2022
DOI: 10.1136/bmjopen-2021-049625
|View full text |Cite
|
Sign up to set email alerts
|

Biological and sociocultural determinants of increased blood pressure among women with a history of gestational diabetes mellitus in rural China: a retrospective cohort study

Abstract: ObjectivesGestational diabetes mellitus (GDM) increases the risk of hypertension and cardiovascular events among mothers later in life. This risk has not been well recognised by healthcare professionals in rural China. Our objectives were to (1) describe the proportion of rural women with increased blood pressure and a history of GDM; and (2) explore the biological and sociocultural factors associated with increased blood pressure.DesignA retrospective cohort study using data from a cross-sectional survey.Sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…We have demonstrated the plausibility of this association that later first pregnancy age might increase the risk of hypertension by adjusting the possible potential factors and stratifying the analysis as much as possible. Furthermore, a previous study showed that one in five rural Chinese postpartum women with a history of gestational diabetes mellitus were found to have elevated blood pressure ( 28 ). The likelihood of early ischemic heart disease and stroke is higher in women with a history of hypertension during pregnancy ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated the plausibility of this association that later first pregnancy age might increase the risk of hypertension by adjusting the possible potential factors and stratifying the analysis as much as possible. Furthermore, a previous study showed that one in five rural Chinese postpartum women with a history of gestational diabetes mellitus were found to have elevated blood pressure ( 28 ). The likelihood of early ischemic heart disease and stroke is higher in women with a history of hypertension during pregnancy ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“… 21 Various types of studies have assigned a significant role to self-efficacy in controlling blood pressure. 20 , 22 , 23 …”
Section: Introductionmentioning
confidence: 99%